2016
DOI: 10.4102/ojvr.v83i1.1136
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of recombinant beta toxin of <i>Clostridium perfringens</i> type B using a commercially available <i>Escherichia coli</i> strain

Abstract: Clostridium perfringens beta toxin is only produced by types B and C and plays an important role in many human and animal diseases, causing fatal conditions that originate in the intestines. We compared the expression of C. perfringens type B vaccine strain recombinant beta toxin gene in the Escherichia coli strains RosettaTM(DE3) and BL21(DE3). The beta toxin gene was extracted from pJETβ and ligated with pET22b(+). pET22β was transformed into E. coli strains BL21(DE3) and RosettaTM(DE3). Recombinant protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Further studies have found that the strain of the E. coli can influence the solubility of the protein. For example, Bakhshi et al [74] found that the rCPB expressed in BL21 (DE3) was insoluble, while that expressed in Rosetta (DE3) was soluble. Reducing the expression temperature (to between 16 and 28 °C) is a common approach by which researchers try to increase protein solubility.…”
Section: Beta Toxin (Cpb)mentioning
confidence: 99%
“…Further studies have found that the strain of the E. coli can influence the solubility of the protein. For example, Bakhshi et al [74] found that the rCPB expressed in BL21 (DE3) was insoluble, while that expressed in Rosetta (DE3) was soluble. Reducing the expression temperature (to between 16 and 28 °C) is a common approach by which researchers try to increase protein solubility.…”
Section: Beta Toxin (Cpb)mentioning
confidence: 99%
“…In recent years, research has been focused on experimental recombinant C. perfringens vaccines. The ETX and cpb gene regions of the C. perfringens have been used for design of the new generation vaccines, separately (Aziminia et al 2016 ; Bakhshi et al 2016 ). Recombinant vaccines expressed in E. coli have resulted in high immunity in laboratory animals (Aziminia et al 2016 ; Lobato et al 2010 ).…”
Section: Vaccine Productionmentioning
confidence: 99%
“…After amplification by PCR reaction, all amplicons were electrophoresed for their qualification in gel electrophoresis (1.0% agarose (Sinaclon, Iran)) (20). The resulting PCR products (about 1.2 kb) were purified by Gel Extraction Kit (Vivantis, Malaysia) according to the manufacturer's recommendations (21,22).…”
Section: Analyzing Of Amplified Pcr Productsmentioning
confidence: 99%